Managing Chaos: The Falklands Campaign 1982. Issue 1 (2nd January 2022) - Macdonald, Roderick
Abstract : I kept a detailed diary throughout the Falklands campaign. When I read my Falklands diary 40 years on, I do not know the author. That person was driven, single-minded and obsessed with winning at all costs, well aware of the global and national implications of both success and failure. I also carried an 8-mm camera and filmed when I could. In 2015, I published this footage with the title, 'Commando Engineers in the Falklands War: Version II', unedited, except for format and subtitles, on YouTube. It was well received. On the voyage home from the conflict, on SS Canberra, I instructed my officers and soldiers to write down their experiences, which were circulated as an after-action report within the Royal Engineers. There was little debriefing on return. The implications of what we had learned were daunting and too expensive to face. We were very tired. We moved on. The focus remained on the British Army of the Rhine. I left the Army in 1993 and moved to the US, where I reside today with my family. We are all US citizens. Since retiring in 2014 after 20 years in business I revisited the Falklands Campaign as a lecturer for the US Marine Corps. Like most veterans, my memories and views have changed over time, as has my knowledge, not least from talking to Argentine veterans and learning from the US Marine Corps. This article reflects my views today on my very real experiences 40 years ago.◼